RESEARCH ON INFORMATION REPRINTING CHARACTERISTICS OF TECHNOLOGY SHARING WECHAT OFFICIAL ACCOUNT-TAKING “PYTHON” AS AN EXAMPLE - Wenhui Lyu; Albattat Ahmad; Mingxia Wei; Zhanling Liu; Weishi Song (Proceedings on Engineering Sciences, 2025)
WeChat official account platform is one of the most important social media platforms for information dissemination, knowledge exchange and product promotion. This paper was designed to analyze the retransmission characteristics of WeChat article official account. Taking 142 WeChat official account and 68,112 articles as examples, this paper investigated the network characteristics, theme co-occurrence and the use of third-party technology of WeChat articles in WeChat official account.The result shows there is an online community formed by article reprinting in WeChat public platform, and the article topics and the use characteristics of third-party class libraries involved in the online community are obvious.